Treatment thresholds for intervention in posthaemorrhagic ventricular dilation: a randomised controlled trial. Issue 1 (10th February 2018) - de Vries, Linda S; Groenendaal, Floris; Liem, Kian D; Heep, Axel; Brouwer, Annemieke J; van 't Verlaat, Ellen; Benavente-Fernández, Isabel; van Straaten, Henrica LM; van Wezel-Meijler, Gerda; Smit, Bert J; Govaert, Paul; Woerdeman, Peter A; et al.
Abstract : Objective: To compare a low versus a higher threshold for intervention in preterm infants with posthaemorrhagic ventricular dilatation. Design: Multicentre randomised controlled trial (ISRCTN43171322 ). Setting: 14 neonatal intensive care units in six countries. Patients: 126 preterm infants ≤34 weeks gestation with ventricular dilatation after grade III–IV haemorrhage were randomised to low threshold (LT) (ventricular index (VI) >p97 and anterior horn width (AHW) >6 mm) or higher threshold (HT) (VI>p97+4 mm and AHW >10 mm). Intervention: Cerebrospinal fluid tapping by lumbar punctures (LPs) (max 3), followed by taps from a ventricular reservoir, to reduce VI, and eventually a ventriculoperitoneal (VP) shunt if stabilisation of the VI below the p97+4 mm did not occur. Composite main outcome measure: VP shunt or death. Results: 19 of 64 (30%) LT infants and 23 of 62 (37%) HT infants were shunted or died (P=0.45). A VP shunt was inserted in 12/64 (19%) in the LT and 14/62 (23%) infants in the HT group. 7/12 (58%) LT infants and 1/14 (7%) HT infants required shunt revision (P<0.01). 62 of 64 (97%) LT infants and 36 of 62 (58%) HT infants had LPs (P<0.001). Reservoirs were inserted in 40 of 64 (62%) LT infants and 27 of 62 (43%) HT infants (P<0.05). Conclusions: There was no significant difference in the primary composite outcome of VP shunt placement or death in infants with posthaemorrhagic ventricular dilatation who were treated at a lower versus a higher threshold for intervention. Infants treated at the lower threshold received more invasive procedures. Assessment of neurodevelopmental outcomes will provide further important information in assessing the risks and benefits of the two treatment approaches.